Dictyosporium duliujiangense sp. nov. (Dictyosporiaceae, Pleosporales) from freshwater habitat in Guizhou Province, China - Liu, Ling-Ling; Song, Lian-Chai; Gu, Xiao-Feng; Wei, Quan-Quan; Zhang, Meng; Liu, Zuo-Yi; Gou, Jiu-Lan (Phytotaxa, 2023)
A survey of the taxonomy and diversity of freshwater fungi from Karst Plateau wetlands in Guizhou Province, China, three fresh collections were collected from a freshwater river. They have cheiroid, digitate, dictyosporous conidia with one or two hyaline appendages. Phylogenetic analysis of the combined ITS, LSU and tef1-α sequence data support their placement with genera Dictyocheirospora and Dictyosporium (Dictyosporiaceae, Pleosporales). Two collections represent the same species, Dictyocheirospora rotunda. The other collection is introduced as a new species Dictyosporium duliujiangense. An updated phylogenetic backbone tree, descriptions and illustrations of the two taxa are provided for Dictyosporiaceae.